Effects of natuzyme® supplementationon fibre digestion, growth and carcass characteristics of male ross 308 broiler chickens - Mashau, Pfuluwani (My University, 2020)
Two experiments were conducted to determine the effect of natuzyme50® supplementation on fibre digestion, growth and carcass characteristics of Ross 308 broiler chickens aged one to 42 days. The first experiment determined the effect of natuzyme50® supplementation on feed intake, growth and live weight of unsexed Ross 308 broiler chickens aged one to 21 days. Unsexed day old chicks were assigned to 4 different natuzyme50® supplementation levels of 0.0 (UNZ0), 0.75 (UNZ0.75), 1.0 (UNZ1.0) and 1.5 (UNZ1.5) g/kg DM feed, replicated 4 times and each replicate having 10 chicks. A general linear model (SAS, 2008) was used to analyse the data. Ross 308 broiler chickens on a diet supplemented with 1.5g of natuzyme50® per kg DM had higher (P<0.05) DM feed intake than those on a diet not supplemented with natuzyme50®. Natuzyme50® supplementation did not (P>0.05) have any significant effect on growth rate of unsexed Ross 308 broiler chickens aged one to 21 days. Unsexed broiler chickens on a diet supplemented with 1.5g of natuzyme50® per kg DM had higher (P<0.05) live weights than those on a diet not supplemented with natuzyme50® at the age of 21 days The second experiment determined the effect of natuzyme50® supplementation on feed intake, growth performance and carcass characteristics of male Ross 308 broiler chickens aged 22 to 42 days. The chickens aged 22 days were assigned to 4 natuzyme50® supplementation levels of 0.0 (MNZ0), 0.75 (MNZ0.75), 1.0 (MNZ1.0) and 1.5 (MNZ1.5) g/kg DM feed, replicated 4 times and each replicate having 6 chickens. The diets were isocaloric and isonitrogenous. A general linear model (SAS, 2008) was used to analyse the data obtained. Natuzyme50® supplementation level had no effect (P>0.05) on feed intake of male Ross 308 broiler chickens aged 22 to 42 days. However, natuzyme50® supplementation level had effect (P<0.05) on growth rate of male Ross broiler chickens aged 22-42 days. Male Ross 308 broiler chickens on a diet supplemented with 1.5g of natuzyme50® per kg DM had higher (P<0.05) growth rates than those on a diet supplemented with 1.0g of natuzyme50® per kg DM. However, the significant differences did not extend to birds on a diet not supplemented with natuzyme50®, diets supplemented with 0.75 or 1.5g of natuzyme50® per kg DM which vi showed similar (P>0.05) growth rates. Natuzyme50® supplementation levels used had no effect (P>0.05) on carcass, breast and drumstick weights of male Ross 308 broiler chickens. Natuzyme50® supplementation levels had no effect (P>0.05) on meat juiciness. However, natuzyme50® supplementation improved (P<0.05) meat tenderness and flavour. Increasing natuzyme50® level of supplementation decreased (P<0.05) meat shear force values. It is concluded that natuzyme50® supplementation improved (P<0.05) meat tenderness and flavour, and reduced meat shear force values of male Ross 308 broiler chickens. However, further studies are recommended to ascertain the current results.
Thesis (M.A. (Agricultural Management) -- University of Limpopo, 2020
Keywords: Natuzyme50® supplementation level; Ross 308 broiler chickens; Fibre digestion; Performance; Broilers (Chickens); Poultry -- Feeding and feeds; Chickens -- Breeding